Antifungal mechanism and transcriptome analysis of Bacillomycin D-C16 against Fusarium oxysporum - Lin, Fuxing; Jiao, Yang; Jiang, Hua; Zheng, Yu; Wu, Shiqin; Zhou, Li; Ren, Xiangmei; Lu, Zhaoxin; Li, Yuanhong (Frontiers in Microbiology, 2025)
BackgroundFusarium oxysporum is a globally distributed soil-borne pathogen that causes substantial economic losses in cash crops. Bacillomycin D-C16, a natural antimicrobial lipopeptide produced by Bacillus subtilis, exhibited potent fungicidal activity against F. oxysporum, with a minimum inhibitory concentration (MIC) of 8 mg/L. However, the precise mechanism of its action against F. oxysporum remains uncharacterized.MethodsIn this study, we employed transmission electron microscopy (TEM) to analyze morphological and ultrastructural alterations in F. oxysporum treated with Bacillomycin D-C16 and RNA-seq profiling combined with biochemical assays to elucidate Bacillomycin D-C16's mode of action against F. oxysporum.ResultsTEM revealed that Bacillomycin D-C16 induced structural disruption of mitochondria in F. oxysporum. Transcriptome analysis identified 3,370 differentially expressed genes (DEGs) in F. oxysporum, comprising 1,488 up-regulated and 1,882 down-regulated genes. Cluster analysis revealed significant changes in gene expression patterns: DEGs associated with mitochondrial function [including oxidative phosphorylation and citrate cycle (TCA cycle) pathways] were down-regulated, while most DEGs involved in glutathione metabolism were up-regulated. Furthermore, nearly all DEGs related to DNA replication were significantly suppressed. Biochemical assays confirmed these observations: Reduced activities of mitochondrial enzymes [malate dehydrogenase (MDH), isocitrate dehydrogenase (IDH), pyruvate dehydrogenase (PDH), and complexes I–V], decreased mitochondrial membrane potential, and diminished ATP content collectively indicated mitochondrial dysfunction. Depleted glutathione (GSH) levels accompanied by elevated glutathione s-transferase (GST) activity, increased malondialdehyde (MDA) content, and accumulated reactive oxygen species (ROS) confirmed disruptions in glutathione metabolism and oxidative stress. Ultraviolet (UV) absorption spectra, fluorescence spectroscopy, and molecular docking simulations demonstrated Bacillomycin D-C16′s preferential binding to the major groove of DNA, leading to abnormal DNA replication.ConclusionsThese findings collectively demonstrate that Bacillomycin D-C16 inhibits F. oxysporum growth through multifaceted mechanisms involving transcriptional regulation, mitochondrial impairment, ROS accumulation, and interference with DNA replication.